2018
DOI: 10.1088/2040-8986/aac68d
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical application of optical fibre sensors

Abstract: Optical fibre sensors (OFS), as a result of their unique properties such as small size, no interference with electromagnetic radiation, high sensitivity and the ability to design multiplexed or distributed sensing systems, have found applications ranging from structural health monitoring to biomedical and point of care instrumentation. While the former represents the main commercial application for OFS, there is body of literature concerning the deployment of this versatile sensing platform in healthcare. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
110
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 220 publications
0
110
0
4
Order By: Relevance
“…Biomolecular optical fiber sensing is based on different processing methods, frequently relying on the interaction of the evanescent field with the external medium. Indeed, as label free detection can be source of significant advances to produce tools for rapid medical diagnosis, a great number of approaches based on surface plasmon resonance (SPR) phenomenon have been developed [15][16][17][18][19][20][21]. Several strategies exist to enable the evanescent field to reach the sensed medium: cladding removed evanescent wave, and tapered or fiber Bragg grating configurations were mainly described.…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular optical fiber sensing is based on different processing methods, frequently relying on the interaction of the evanescent field with the external medium. Indeed, as label free detection can be source of significant advances to produce tools for rapid medical diagnosis, a great number of approaches based on surface plasmon resonance (SPR) phenomenon have been developed [15][16][17][18][19][20][21]. Several strategies exist to enable the evanescent field to reach the sensed medium: cladding removed evanescent wave, and tapered or fiber Bragg grating configurations were mainly described.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of physiological processes and early detection of certain diseases [1] requires sensors capable of probing subtle changes in temperature [2], pH level [3,4], and concentration of biological fluids and gases [3] in hard-to-reach places inside living organisms such as the brain [5], spinal cord [6], ovarian tract [7] and blood vessels [8]. Such changes can often be sensed as small shifts in the optical refractive index of bodily fluids and tissues [8].…”
Section: Introductionmentioning
confidence: 99%
“…A non-wearable medical device Dermalab ® trans-epidermal water loss (Cortex Technology, DK) was used as a reference. It is suggested that a distributed body network could be established to provide valuable information for improving athletes' physical performance.Compared to electronic humidity sensors, an optical fibre sensor (OFS) offers several advantages such as light weight, miniature size, flexibility, simple configuration and insensitivity to electromagnetic fields [9]. The diameter of a single mode optical fibre is typically 125 µm which is smaller than many textile yarns meaning the OFS can be embedded into garments for wearable sensing applications [9].…”
mentioning
confidence: 99%
“…It is suggested that a distributed body network could be established to provide valuable information for improving athletes' physical performance.Compared to electronic humidity sensors, an optical fibre sensor (OFS) offers several advantages such as light weight, miniature size, flexibility, simple configuration and insensitivity to electromagnetic fields [9]. The diameter of a single mode optical fibre is typically 125 µm which is smaller than many textile yarns meaning the OFS can be embedded into garments for wearable sensing applications [9]. A range of different approaches for optical fibre humidity sensing have been proposed [10] including interferometers [11], evanescent wave interactions [12], in-fibre gratings (Bragg and long period gratings) [13][14][15], carbon nanotubes [16], photonic crystal fibres [17] and reflection measurements [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation